Knowledge, attitude and practice towards cervical cancer screening among women living with human immunodeficiency virus: Implication for prevention strategy uptake. Issue 4 (9th November 2022) - Mukosha, Moses; Muyunda, Daniel; Mudenda, Steward; Lubeya, Mwansa Ketty; Kumwenda, Andrew; Mwangu, Luwi Mercy; Kaonga, Patrick
Abstract: Aim: To explore the knowledge, attitude and practices of cervical cancer screening among HIV‐infected women in public health facilities in Lusaka, Zambia. Design: Cross‐sectional study. Methods: The study was conducted from 1st January 2020 to 28th February 2020. We used a structured questionnaire for data collection. The Structural Equation Modelling (SEM) was used to analyse relationships among latent variables (knowledge, attitude and practice). Results: The overall knowledge, attitude, and practice scores of cervical cancer screening among women living with HIV were 6.86/11 (62.4%), 6.41/7 (91.6%) and 2.92/8 (36.5%), respectively. Overall, knowledge was positively and significantly associated with attitude ( r = .53, p < .001) and practice ( r = .38, p < 0.001). Additionally, attitude and practice were significantly associated (r = 0.29, p < .001). Our findings support the reinforcement of current public health interventional programmes to improve the knowledge about cervical cancer and screening uptake.